ZOOPLANKTON SPATIAL DISTRIBUTION AND COMMUNITY STRUCTURE IN BANGGAI SEA - Arief Rachman; Elly Asniariati (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2012)
Banggai Sea is an interesting ecosystem due to mixing influences from Banda Sea in the west and Maluccas Sea in the east. Therefore, a unique zooplankton community structure and specific distribution pattern should be found in this area. This research was carried on using Baruna Jaya VIII research vessel and samples were collected in 14 sampling stations. Vertical towing using NORPAC plankton net (300 μm) was conducted to collect zooplankton samples. Result showed that inner Mesamat Bay had the lowest abundance of zooplankton, probably due to low water quality resulted from anthropogenic activity. Meanwhile the strait between Liang and Labobo Island had the highest zooplankton abundance in Banggai Sea. Calanoids was the dominant zooplankton taxa in the ecosystem and contributing 55.7% of total density of zooplankton community. The highest importance value made this taxa to be very important factor that regulates the lower trophic level organisms. Results also showed that zooplankton was distributed nearly uniform in eastern but aggregated to several stations in western Banggai Sea. Zooplankton abundance was higher in the central of Banggai Sea, compared to western and eastern area. According to Bray-Curtis clustering analysis the strait between Liang and Labobo Island has unique zooplankton community structure. This might happened due to mixing of water from two highly productive seas that influenced the Banggai Sea ecosystem. From this research we conclude that this strait probably was the zooplankton hot spot area which might also indicate that this area also a hot spot of fishes in the Banggai Sea.Keywords: spatial distribution, zooplankton, community structure, hot spot, Banggai